Intervista a Walter Panciera: Insegnare il metodo storico e la sua utilità - Massimo Galtarossa (Firenze University Press, 2021)
The interview with one of the major specialists in Didactics of modern italian History concerns the subject of teaching the discipline, renewed since the late nineties of the XIX centurythanks to the emergence of new historiographical addresses, advancements in the legislative field and the contribution of pedagogical disciplines. The manual, a controversial but valuable literary genre, remains a useful teaching tool for a new teaching profession, which contemplates a more precise awareness of the historical method and its implications. The history laboratory appears to be the place where the use of sources, experimentations, interdisciplinarity and problematicity are highlighted; further, today the problem arises of breaking into the educational systems from everyday reality. Thus, even the Eighteenth-century cultural debate, such as the history of colonization or epidemics, can undoubtedly contribute to the formation of a citizen who is aware and oriented on the level of historical vision.